A low-cost flow cytometric assay for the detection and quantification of apoptosis using an anionic halogenated fluorescein dye. (September 2008) - Meyer, Mervin; Essack, Magbubah; Kanyanda, Stonard; Rees, Jasper G.
We describe here a technical improvement of an established colorimetric method used to detect and measure the occurrence of apoptosis in mammalian cells during in vitro cell culture. This assay uses an anionic halogenated fluorescein dye that is taken up by apoptotic cells at the stage of phosphatidylserine externalization. We demonstrate that apoptotic cells stained with this dye can be detected by flow cytometric analysis. Furthermore, we show that the modified method compares well with the standard annexin-V–based apoptosis assay and that it is significantly more cost-effective than the annexin-V assay.